Surface Plasmon Polariton-coupled Waveguide Back Reflector in Thin-film Silicon Solar Cell - Prabhathan, Patinharekandy (2016)
Surface plasmon polariton (SPP) waveguide-coupled back reflector geometry is proposed for efficient light trapping and broadband absorption enhancement in thin-film silicon solar cells. The proposed geometry takes advantage of the localized surface plasmon (LSP) enhancement, Fabry-Perot (FP) resonance, and strong electric field confinement resulting from the SPP interference in a metal waveguide. It is shown that the designed light trapping structures contribute to significant light trapping and enhancement in the red to near-infrared part of the solar spectrum. For a thin-film silicon solar cell of 220-nm thickness, an absorption enhancement of 153 % is obtained when compared to a bare silicon solar cell. In comparison to other SPP-excited back reflection geometries, such as nano-gratings and nano-grooves, the proposed configuration shows a higher absorption enhancement factor and uniform field distribution inside the silicon layer. These results are expected to introduce new directions in the design of optimized nanoscale back reflectors in thin-film silicon solar cells.